Perlindungan Hukum terhadap Anak Korban Kekerasan Seksual (Studi di Desa Sabrang Kecamatan Ambulu Kabupaten Jember) - Mohammad Hafidz; Firda Laily Mufid (Fakultas Hukum Universitas Islam Jember, 2018)
Sexual violence against children is one of the new forms of evil, which concerns children as the next generation of the nation, resulting in considerable evil among the people. Sexual violence is not only happening in the larger cities of relatively advanced culture and awareness or legal knowledge, but also occurs in rural areas that still hold the value of tradition and customs. Sexual assault cases that occurred in Sabrang Village Ambulu Sub-district Jember District make the child of 6 (six) as a victim of inappropriate behavior by the sodomy perpetrator. In the case of a child as a victim of a crime of sexual violence in this case is an abuser committed by the people nearest the victim, then the child is also the person who saw, heard and witnessed the incident. Because in general, crimes against morality there are only perpetrators and victims who automatically victim also provides testimony of criminal acts perpetrated by the perpetrator.